Towards a politics of the media: The role of the image in the Velasco Alvarado regime (1968-1975) - Rubio Bautista, Douglas Javier (2021)
The present work consists of analyzing the existence of a communication policy in the Velasco Alvarado regime (1968-1975). The objective of the design of this policy was to disseminate the cultural proposals of the regime from the principle of refounding a new Peruvian nation. Given this, we distinguish two key concepts for this article: culture and the media. For this proposal, the media are instruments that use codes designed to disseminate messages articulated with the nationalism of the military regime. From this instrumentalization, Velasquismo will generate a political framework to manage the visual image, a key communication unit for its nationalist propaganda. The reasons for this perception were manifested in a context that we will review in this work: authoritarianism and state interventionism, an artistic scene with an avant-garde bias and a depoliticized society like Peru’s in the 70s.